2021
DOI: 10.1080/14712598.2021.1908995
|View full text |Cite
|
Sign up to set email alerts
|

AIRMESS – Academy of International Regenerative Medicine & Surgery Societies: recommendations in the use of platelet-rich plasma (PRP), autologous stem cell-based therapy (ASC-BT) in androgenetic alopecia and wound healing

Abstract: Introduction: Many investigations showed that platelet-rich plasma (PRP), human follicles stem cells (HFSCs), and adipose-derived stem cells (ASCs), considered autologous stem cell-based therapy (ASC-BT), are effective for hair regrowth (HR) in patients affected by androgenetic alopecia and for wound healing (WH). The aim of this article is to analyze the in vitro and in vivo impact of different PRP, HFSCs, and ASCs preparation methods on HR and in WH. Areas Covered: The analyzed data intended to clarify the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Further, combined PRP and human follicle MSCs positively influenced hair growth, stimulated hair follicle development, and suppressed apoptosis [ 84 ]. Of note, Gentile et al provided an evidence of therapeutic positive outcomes of autologous stem cell-based therapy including PRP, human follicle stem cells, and adipose-derived stem cells in wound healing and hair regrowth [ 85 ]. PRP was also applied in oral and maxillofacial surgery [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, combined PRP and human follicle MSCs positively influenced hair growth, stimulated hair follicle development, and suppressed apoptosis [ 84 ]. Of note, Gentile et al provided an evidence of therapeutic positive outcomes of autologous stem cell-based therapy including PRP, human follicle stem cells, and adipose-derived stem cells in wound healing and hair regrowth [ 85 ]. PRP was also applied in oral and maxillofacial surgery [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…An expert opinion on the effects of PRP and autologous stem cell therapy noted that hair regeneration and wound healing share many common molecular pathways, especially the stimulation of Wnt/b-catenin signalling [26], that are similarly influenced by ALRV5XR. A meta-analysis of clinical trials of PRP in men and women found a mean efficacy of change in total hair count of 23.5 (95%CI: 9.9À37.1) hairs/cm 2 , however within 9À12 months of completing PRP or stem cell therapy, the gains in hair density decline by approximately 50% [16,26].…”
Section: Discussionmentioning
confidence: 99%
“…An expert opinion on the effects of PRP and autologous stem cell therapy noted that hair regeneration and wound healing share many common molecular pathways, especially the stimulation of Wnt/b-catenin signalling [26], that are similarly influenced by ALRV5XR. A meta-analysis of clinical trials of PRP in men and women found a mean efficacy of change in total hair count of 23.5 (95%CI: 9.9À37.1) hairs/cm 2 , however within 9À12 months of completing PRP or stem cell therapy, the gains in hair density decline by approximately 50% [16,26]. When considering the initial rapid hair regrowth effect followed by a decline in hair density after PRP and stem cell therapy [23,26], studying the use of ALRV5XR as an adjuvant for pre and post PRP or stem cell therapy, may offer a potentiating effect to enhance or sustain the hair density improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the introduction of PRP improved hair regrowth by autologous human follicle MSC therapy in androgenetic alopecia [ 84 ]. The effects of autologous non-activated PRP and activated PRP in wound healing and hair regrowth were evaluated [ 85 ], and in 2021, the Academy of International Regenerative Medicine and Surgery Societies (AIRMESS) recommendations on the use of platelet-rich plasma (PRP) and autologous stem cell-based therapy (ASC-BT) in androgenetic alopecia and wound healing were released [ 86 ].…”
Section: Mesenchymal Stem Cell Therapy (Msct)mentioning
confidence: 99%